Two Prayer Books - Not Two Tongues: A reply to Dr. Hayes - Barnett, T. A. M. (Toronto journal of theology, 1991)
Alan Hayes chose an intriguing title for his essay on prayer books: "Praying in Two Tongues''. By free association it reminds me of the hymn "O for a thousand tongues to sing /My dear redeemer's praise." Yet many advocates of prayer books, including Alan Hayes, do not want even two tongues. He claims in his article, subtitled "Conflicting Principles of Worship in the Anglican Church of Canada", that the Anglican Church suffers from a "liturgical and liturgiological split personality." From the title, the body of the essay and remarks made by Hayes in a recent lecture in Ottawa, I judge that he rather favours the Book of Common Prayer (BCP), and deplores the Book of Alternative Services (BAS). He does, however ask very pertinent questions about both books. I will confine my answer to them here to some basic principles.